Hubungan Antara Kecekapan Modal Insan dengan Keberkesanan Program Kreativiti dan Inovasi Anjuran Perbadanan Produktiviti Malaysia (MPC) - Muhammad Suffian, Ahmad (2013)
The purpose of this research is to examine the relationship of the human capital efficiency towards the effectiveness of the creativity and innovation programmes organized by Malaysia Productivity Corporation (MPC). This research was quantitative in nature where data were gathered using survey questionnaire. A total of 374 respondents from the participants who involved in the conventions, mini conventions and Innovative and Creative Circle (ICC) programmes organized by the Malaysia Productivity Corporation (MPC) in 2012 participated in this study. In this study, descriptive and inferential analysis was applied. Descriptive analysis is used to analyze the demographic and identify the levels of the variables involved. Inferential analysis involves regression analysis as the main analyses to determine the effect between the efficiency of human capital and the effectiveness of the productivity and quality programmes organized by MPC. In conclusion, there is a positive relationship and influence as well as significant differences between the human capital efficiency towards the effectiveness of the creativity and innovation programmes organized by MPC.